SynNotch-CAR T cells overcome challenges of specificity, heterogeneity, and persistence in treating glioblastoma - Choe, Joseph H; Watchmaker, Payal B; Simic, Milos S; Gilbert, Ryan D; Li, Aileen W; Krasnow, Nira A; Downey, Kira M; Yu, Wei; Carrera, Diego A; Celli, Anna; Cho, Juhyun; Briones, Jessica D; et al. (Science translational medicine, 2021)
Treatment of solid cancers with chimeric antigen receptor (CAR) T cells is plagued by the lack of ideal target antigens that are both absolutely tumor specific and homogeneously expressed. We show that multi-antigen prime-and-kill recognition circuits provide flexibility and precision to overcome these challenges in the context of glioblastoma. A synNotch receptor that recognizes a specific priming antigen, such as the heterogeneous but tumor-specific glioblastoma neoantigen epidermal growth factor receptor splice variant III (EGFRvIII) or the central nervous system (CNS) tissue-specific antigen myelin oligodendrocyte glycoprotein (MOG), can be used to locally induce expression of a CAR. This enables thorough but controlled tumor cell killing by targeting antigens that are homogeneous but not absolutely tumor specific. Moreover, synNotch-regulated CAR expression averts tonic signaling and exhaustion, maintaining a higher fraction of the T cells in a naïve/stem cell memory state. In immunodeficient mice bearing intracerebral patient-derived xenografts (PDXs) with heterogeneous expression of EGFRvIII, a single intravenous infusion of EGFRvIII synNotch-CAR T cells demonstrated higher antitumor efficacy and T cell durability than conventional constitutively expressed CAR T cells, without off-tumor killing. T cells transduced with a synNotch-CAR circuit primed by the CNS-specific antigen MOG also exhibited precise and potent control of intracerebral PDX without evidence of priming outside of the brain. In summary, by using circuits that integrate recognition of multiple imperfect but complementary antigens, we improve the specificity, completeness, and persistence of T cells directed against glioblastoma, providing a general recognition strategy applicable to other solid tumors.